Veneration of Venus in Augustan love poetry as a metaphor of total devotion. Issue 1 (2nd January 2023) - Rüpke, Jörg
ABSTRACT: Poets like Horace, Tibullus, Propertius, and Ovid spoke about emotional and explicitly sexual relationships with Venus in a language mobilising towards radical ways to live. Criminal actions from prayer attacks to the use of poisons were considered and imagined as being performed in this literature. Whereas the phenomenon of militia amoris – sexual relationships of men to women framed as military service – has been studied extensively, it has never been analysed in a framework of the History of Religion. Given the widespread reception of such texts and the rise of concepts of militia Christiana in the later Empire, a closer look at these texts is necessary. Focusing on Horace, Odes 4.1, this article inquires into his construction of the interplay of total devotion and emotions, which lies at the basis of performances of this text, and into the coherency of the religious framework developed in the poetry.